Cutaneous mechanoreceptor feedback from the hand and foot can modulate muscle sympathetic nerve activity - Strzalkowski, Nicholas D.; Incognito, Anthony V.; Bent, Leah; Millar, Philip J. (Frontiers in Neuroscience, 2016)
Stimulation of high threshold mechanical nociceptors on the skin can modulate efferent sympathetic outflow. Whether low threshold mechanoreceptors from glabrous skin are similarly capable of modulating autonomic outflow is unclear. Therefore, the purpose of this study was to examine the effects of cutaneous afferent feedback from the hand palm and foot sole on efferent muscle sympathetic nerve activity (MSNA). Fifteen healthy young participants (9 male; 25 ± 3 years [range: 22-29]) underwent microneurographic recording of multi-unit MSNA from the right fibular nerve during 2 minutes of baseline and 2 minutes of mechanical vibration (150Hz, 220μm peak-to-peak) applied to the left hand or foot. Each participant completed three trials of both hand and foot stimulation, each separated by 10 minutes. MSNA burst frequency decreased similarly during the two minutes of both hand (20.8 ± 8.9 vs. 19.3 ± 8.6 bursts/minute [ -8%], p=0.035) and foot (21.0 ± 8.3 vs. 19.5 ± 8.3 bursts/minute [ -8%], p=0.048) vibration but did not alter normalized mean burst amplitude or area (All p>0.05). Larger reductions in burst frequency were observed during the first 10 seconds (onset) of both hand (20.8 ± 8.9 vs. 17.0 ± 10.4 [ -25%], p<0.001) and foot (21.0 ± 8.3 vs. 18.3 ± 9.4 [ -16%], p=0.035) vibration, in parallel with decreases in normalized mean burst amplitude (hand: 0.45 ± 0.06 vs. 0.36 ± 0.14% [ -19%], p=0.03; foot: 0.47 ± 0.07 vs. 0.34 ± 0.19% [ -27%], p=0.02) and normalized mean burst area (hand: 0.42 ± 0.05 vs. 0.32 ± 0.12% [ -25%], p=0.003; foot: 0.47 ± 0.05 vs. 0.34 ± 0.16% [ -28%], p=0.01). These results demonstrate that tactile feedback from the hands and feet can influence efferent sympathetic outflow to skeletal muscle.